TEKNIK MEMAHAMI PERKEMBANGAN PESERTA DIDIK DI SD GMIT 007 KABOLA - Cindy Sintikhe Dollu; Bendelina Marta Malailo, Andri Makalbani, Yessy Matta, Petrus Mau Tellu Dony, Yermia S. Wabang (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to describe techniques for understanding student development at GMIT 007 KABOLA Elementary School in an effort to support optimal student development. Guidance in elementary schools plays a crucial role in shaping character, increasing learning motivation, and helping students overcome academic and socio-emotional difficulties. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that techniques for understanding student development at GMIT 007 KABOLA Elementary School have been implemented in a structured manner through a guidance planning program, character and learning training activities, and ongoing evaluation. The mentoring system includes the involvement of the principal, class teachers, parents, and the local community. However, challenges remain in terms of limited specialized guidance experts and supporting facilities. Therefore, increased teacher training in guidance services and collaboration with external parties are needed to support the effectiveness of the guidance program. These findings have significant implications for the development of holistic and contextual guidance management at the elementary school level.